Climate warming and agricultural stressors interact to determine stream periphyton community composition. (9th July 2014) - Piggott, Jeremy J.; Salis, Romana K.; Lear, Gavin; Townsend, Colin R.; Matthaei, Christoph D.
Abstract: Lack of knowledge about how the various drivers of global climate change will interact with multiple stressors already affecting ecosystems is the basis for great uncertainty in projections of future biological change. Despite concerns about the impacts of changes in land use, eutrophication and climate warming in running waters, the interactive effects of these stressors on stream periphyton are largely unknown. We manipulated nutrients (simulating agricultural runoff), deposited fine sediment (simulating agricultural erosion) (two levels each) and water temperature (eight levels, 0–6 °C above ambient) simultaneously in 128 streamside mesocosms. Our aim was to determine the individual and combined effects of the three stressors on the algal and bacterial constituents of the periphyton. All three stressors had pervasive individual effects, but in combination frequently produced synergisms at the population level and antagonisms at the community level. Depending on sediment and nutrient conditions, the effect of raised temperature frequently produced contrasting response patterns, with stronger or opposing effects when one or both stressors were augmented. Thus, warming tended to interact negatively with nutrients or sediment by weakening or reversing positive temperature effects or strengthening negative ones. Five classes of algal growth morphology were all affected in complex ways by raised temperature, suggesting that these measures may prove unreliable in biomonitoring programs in a warming climate. The evenness and diversity of the most abundant bacterial taxa increased with temperature at ambient but not with enriched nutrient levels, indicating that warming coupled with nutrient limitation may lead to a more evenly distributed bacterial community as temperatures rise. Freshwater management decisions that seek to avoid or mitigate the negative effects of agricultural land use on stream periphyton should be informed by knowledge of the interactive effects of multiple stressors in a warming climate.